El Proceso Audiovisual en el Desarrollo del Aprendizaje en los niños del quinto año paralelo “B” de la Escuela Martiniano Guerrero Freire, en el Periodo Académico 2017-2018 - Bonilla Padilla, Jonathan Eduardo (2018)
This research was oriented to determinate how the audiovisual processes develop the Learning in fifth-grade children from parallel “B” of a school called Martiniano Guerrero Freire, in the academic period 2017-2018, both the problem and its approach allows to have a clear idea about the use of these media. This research is based on the identification, analysis, and investigation of various audiovisual media that help the teaching-learning process, such as radio, television, internet, among others. Since they are part of the so-called multisensory didactic resources that attempt to approximate teaching to direct experience using the perception, hearing and sight pathways; in this way, the audiovisual medium recreated images, words and sounds, followed by an analysis as the stages of development manifest according to Piaget, which emphasizes concrete operations to help the learning development. When referring to the methodology, the design of the research is no-experimental and documentary, the type according to the level is descriptive; for the place it is of field and bibliography, the population is of 30 children, with the survey technique and the questionnaire as instrument for the data collection, with an analysis of tables and statistical graphs were concluded that many of these audiovisual media are not used by teachers to help in learning process due to lack of planning, lack of knowledge. Therefore, it is recommended that teachers update in the use of these audiovisual media and use them in class.